E-5: SINO - RUSSIA RELATIONSHIP: EMERGING CHALLENGES TO THE UNITED STATES OF AMERICA - Kumari , Lubna; Rafique, M.Umair (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2024)
This research paper explains the growing strong ties and cooperation between China and Russia. By analyzing the relative positions of the two states in the international system, this research attempts to solve this conundrum. This paper attempts to find out how China and Russia jointly challenge the United States of America. China is hesitant to challenge the hegemonic order put in place by the United States because it can expand and prosper by free-riding on it. Russia is not happy with the current situation and is determined to change it to stop its decline and keep its great power position. The study is carried out through the secondary sources available online and it reveals that Currently China is an economically strong nation state and China’s cooperation with Russia is giving a tough time to the United States. At the same time, Russia’s international position has been weakened by Vladimir Putin’s deliberate war in Ukraine, which has also damaged the well-crafted image of great-power strength that Putin has spent two decades cultivating. But America may not necessarily benefit from Russia’s decline in relative strength. This study attempts to determine whether the foundations of the alliance between the two countries are defensive and role-playing against the United States.